SOSIALISASI NANOEMULGEL ANTIBAKTERI KOMBINASI EKSTRAK TEMULAWAK DAN TEMUPUTIH UNTUK MENGATASI INFEKSI MRSA DI DESA PAYAMABAR - Diding Pradita; Reza Destri Anggi; Azzura Ligo; Puspita Kusuma Wardani, Dea; Aminah, Nurul (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
Infections caused by Methicillin-Resistant Staphylococcus aureus (MRSA) remain a major health concern due to their resistance to commonly used antibiotics, driving interest in safe and effective natural-based alternatives. This community service program introduced an antibacterial nanoemulgel formulated from combined extracts of Curcuma xanthorrhiza (temulawak) and Curcuma zedoaria (temu putih) to residents of Paya Mabar Village, Stabat District, Langkat Regency. The activities included interactive education on the dangers of bacterial resistance, a demonstration of nanoemulgel preparation, and small group discussions to explore participants’ understanding of modern herbal-based treatments. Community members showed strong enthusiasm, reflected in active participation and improved awareness of antibiotic resistance and the potential of local medicinal plants. The outcomes indicated that a combined educational and hands-on approach effectively enhanced public knowledge of infection prevention and encouraged appreciation for natural ingredients as innovative health solutions. The community recognized nanoemulgel as a bridge between traditional wisdom and modern pharmaceutical technology.